2011
DOI: 10.1128/jb.06412-11
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Central Carbon and Energy Metabolism in Bacteria by Redox-Responsive Repressor Rex

Abstract: Redox-sensing repressor Rex was previously implicated in the control of anaerobic respiration in response to the cellular NADH/NAD ؉ levels in Gram-positive bacteria. We utilized the comparative genomics approach to infer candidate Rex-binding DNA motifs and assess the Rex regulon content in 119 genomes from 11 taxonomic groups. Both DNA-binding and NADsensing domains are broadly conserved in Rex orthologs identified in the phyla Firmicutes, Thermotogales, Actinobacteria, Chloroflexi, Deinococcus-Thermus, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
215
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(222 citation statements)
references
References 40 publications
7
215
0
Order By: Relevance
“…gov/nuccore/NZ_GL877878.1), was blasted with rex in Saccharopolyspora erythraea, Streptomyces coelicolor, and Streptomyces avermitilis by using the BLASTP algorithm with significant sequence similarity (E value < 10 −40 ). The rex gene in the S. spinosa genome sequencing was identified (Additional file 1: Figure S1) [15]. By blasting genes located in the downstream of rex with the genome of Saccharopolyspora erythraea, Streptomyces coelicolor, and Streptomyces avermitilis, we found that genes located in the downstream of rex were cytochrome bd oxidase synthesis gene, cytAB.…”
Section: Rex and Cytochrome Bd Oxidase Genes Determination And Expresmentioning
confidence: 99%
See 1 more Smart Citation
“…gov/nuccore/NZ_GL877878.1), was blasted with rex in Saccharopolyspora erythraea, Streptomyces coelicolor, and Streptomyces avermitilis by using the BLASTP algorithm with significant sequence similarity (E value < 10 −40 ). The rex gene in the S. spinosa genome sequencing was identified (Additional file 1: Figure S1) [15]. By blasting genes located in the downstream of rex with the genome of Saccharopolyspora erythraea, Streptomyces coelicolor, and Streptomyces avermitilis, we found that genes located in the downstream of rex were cytochrome bd oxidase synthesis gene, cytAB.…”
Section: Rex and Cytochrome Bd Oxidase Genes Determination And Expresmentioning
confidence: 99%
“…Studies have demonstrated that the rex regulator responds to intracellular NADH/NAD + levels and controls the expression of genes involved in lots of metabolisms in Actinomycetales [15]. The complete genome of S. spinosa ATCC 49460, accession number NZ_GL877878 in the NCBI nucleotide database (http://www.ncbi.nlm.nih.…”
Section: Rex and Cytochrome Bd Oxidase Genes Determination And Expresmentioning
confidence: 99%
“…Several of these genes are also regulated by the redox response regulator Rex. 26 Most of the oxidative phosphorylation genes have a profile that indicates that they are repressed by PhoP following phosphate depletion, whereas the nitrate reductase genes are activated. 4,19 These results suggest that depletion of phosphate results in a switch from aerobic respiration to nitrate respiration.…”
Section: Genetic Basis Of Phosphate Control Of Metabolismmentioning
confidence: 99%
“…Moreover, the oxidative phosphorylation genes contain sequences that are recognized by both, PhoP and the Rex regulator. 26 Similarly, in chitin metabolism, a regulatory protein, DasR, binds to promoter regions involved in N-acetylglucosamine metabolism that are also regulated by PhoP. 41 The interaction of regulatory proteins may estabilize the binding of PhoP to weakly conserved PHO boxes and explains why there are so many PhoPbinding regions detected in the DNA by the ChIP-on-chip technique.…”
Section: Binding Of Two Regulatory Proteins To Close Positions In Thementioning
confidence: 99%
“…They regulate the oxidation state of the NAD pool and control product formation by binding to operons upstream of genes which code primarily for hydrogenases and cytochromes when the NADH:NAD+ ratio is low, preventing production of enzymes that oxidize NADH ( Figure 9). Forms of Rex have been found to be highly conserved across many species of bacteria, including aerobes and anaerobes, and span a wide range of distantly related taxonomic groups 104 . In function, it has been found that Rex enzymes are either inhibited by NADH 99 or activated by NAD +102 , though the outcome of down-regulating NADH oxidation is the same.…”
Section: Repressor Enzymesmentioning
confidence: 99%